ʻĀina hānau = Birth land - McDougall, Brandy Nālani (Sun tracks, 2023)
"'Āina Hānau / Birth Lands is a powerful collection of new poems by Kanaka ʻŌiwi (Native Hawaiian) poet Brandy Nālani McDougall. These poems cycle through sacred and personal narratives while exposing and fighting ongoing American imperialism, settler colonialism, militarism, and social and environmental injustice to protect the ʻāina and its people"--